Calcific pancreatitis uncovering a multiple endocrine neoplasia type 1: A case report in compliance with the scare guidelines. (2020) - Rahou, F.; Miry, A.; Mirali, H.; Mahmoudi, L.; Bennani, A.; Bouziane, M.
Highlights: Hypercalcemia found on a routine blood work should aggregate the systematic endocrine explorations; Primary hyperparathyroidism is first in line. Calcifying pancreatitis is linked to hyperparathyroidism but the mechanism is not fully elaborated, the inflammation can be chronic or acute but it definitely indicates a long term evolution of the hypercalcemia. Parathyroidectomy cures the hyperparathyroidism and ensure the control of the hypercalcemia but no study has studied the long term evaluation of the pancreatitis. Abstract: Introduction: Chronic pancreatitis are mostly linked to alcoholic consumption or biliary lithiasis; and Primary hyperthyroidism (PHPT) is still a very rare association and the exact physiopathology is yet to be fully unveiled to the human knowledge. We present the first case report of a calcific pancreatitis associated with not only PHPT but a multiple endocrine neoplasia (MEN) type 1. Case presentation: We report the case of a 52 years old woman suffering from mellitus diabetes consulting the emergency rooms for acute pancreatitis with hyperlipasemia and hypercalcemia whom final imaging discovered a pituitary gland adenoma, a left surrenal adenoma, and a parathyroid adenoma, and for the pancreas it reveiled an acute mild pancreatitis with a background of calcifications, no gallstones, no bone or renal abnormalities; and the parathyroidectomy was performed following the minimally invasive selective technique. Discussion: Calcemia levels testing routinely performed help discover hyperparathyroidism. The associations of chronic pancreatic inflammation to hyperparathyroidism needs to be studied, even if hypercalcemia is prooven to be a risk factor of pancreatitis; the mechanism behind this association is brievely described. parathyroidectomy is the definitive cure for hyperparathyroidism, the technique advances has shown effective localization of the responsible adenoma and the intraoperative testing of parathormon levels after resection decreasing is a very reliable extemporaneous sign for the success of the procedure. Conclusion: The endocrine system is synchronized; meaning the injury of one gland should start the search for others. In our case, the first main lead should not have been the acute pancreatitis but her diabetes. In the future we suggest that diabetes primary explorations may need a pancreatic imaging and endocrine explorations even though it could get pricier for the healthcare system, but giving the complications that we could prevent; it is to be considered.